Auditory spatial attention in younger and older adults: A comparison of laboratory and self-report measures - Singh, Gurjit; Pichora-Fuller, M.Kathleen (Canadian Acoustics, 2007)
A comparison between laboratory and self-report measures in auditory spatial attention in younger and older adults are studied. Younger adult and older adult listeners with normal audiometric thresholds in the speech range were studied who were simultaneously presented with a target sentence and two competing sentences. Each sentence was presented from one of three different loudspeaker locations. Target call sign identity was defined on a visual display either before or after sentences were presented. One of four different probability specifications was visually displayed to indicate the likelihood of the target being presented at the left, center, and right locations. Comparing performance on likely and unlikely trials, it was found that although younger adults performed better than older adults by an average of 9%, the cost of switching attention was equivalent for older and younger adults, suggesting a lack of age-related differences in the suggesting ability to switch attention when listening in a multi-talker environment.